Chimeric antigen receptor T-cell therapy-induced nervous system toxicity: a real-world study based on the FDA Adverse Event Reporting System database - Xiayang Ren; Guanmin Zhang; Guohui Li; Yanfeng Wang (BMC Cancer, 2024)
Abstract Background Nervous system toxicity (NST) is one of the most frequent and dangerous side effects of chimeric antigen receptor T-cell (CAR-T) therapy, which is an effective treatment for related tumors in most relapsed/refractory (r/r) hematologic malignancies. Current clinical trial data do not fully reflect the real-world situation. Therefore, this study evaluated the NST of CAR-T therapy using the FDA Adverse Event Reporting System (FAERS). Methods Data were retrieved from FAERS for the period from January 1, 2017 to March 31, 2023. Disproportionality analysis and Bayesian analysis were used for data mining. The reporting odds ratio (ROR) for NST with 95% confidence interval (CI) was calculated for each CAR-T product. The time to onset (TTO) and clinical outcomes due to CAR-T therapy-associated NST were assessed. Results Overall, 6946 cases of NST associated with CAR-T therapy were identified. The patients had a median age of 61 years (interquartile range [IQR]: 47–69 years). Significant signals were observed for all CAR-T products (ROR: 2.19, 95% CI: 2.13–2.44). Anti-CD19 CAR-T products showed a higher NST signal than anti-B cell maturation antigen (BCMA) CAR-T products (ROR025 2.13 vs. 1.98). Brexucabtagene autoleucel (ROR: 3.17, 95% CI: 2.90–3.47) and axicabtagene ciloleucel (ROR: 2.92, 95% CI: 2.81–3.03) had the two highest NST signals. For the preferred term “brain edema,” the highest signals were obtained for CD28 CAR-T products. The median TTO of NST for all CAR-T products was 7 days (IQR: 3–17 days). The proportion of death, life-threatening and hospitalization adverse events associated with NST was 20.06%, 7.21%, and 32.70%, respectively. The proportion of death outcomes was higher in patients treated with tisagenlecleucel (30.36%) than in those treated with other CAR-T products, except ciltacabtagene autoleucel (P < 0.001). The proportion of hospitalizations was significantly higher for lisocabtagene maraleucel-associated NST (53.85%) than for other drugs, except for ciltacabtagene autoleucel (P < 0.001). Conclusions NST is more closely associated with anti-CD19 CAR-Ts and CAR-Ts containing CD28. Serious NST (brain oedema) is likely to occur with CAR-Ts that contain CD28. CAR-T-related NST warrants greater attention owing to the high proportion of serious adverse events and delayed NST.